Collapse phase diagram of carbon nanotubes with arbitrary number of walls. Collapse modes and macroscopic analog. (30th June 2021) - Magnin, Y.; Rondepierre, F.; Cui, W.; Dunstan, D.J.; San-Miguel, A.
Abstract: Carbon nanotubes tend to collapse when their diameters exceed a certain threshold, or when a sufficiently large external pressure is applied on their walls. The radial stability of tubes has been studied in each of these cases, however a general theory able to predict collapse is still lacking. Here, we propose a simple model predicting stability limits as a function of the tube diameter, the number of walls and the pressure. The model is supported by atomistic simulations, experiments, and is used to plot collapse phase diagrams. We have identified the most stable carbon nanotube, which can support a maximum pressure of ∼ 18 GPa before collapsing. The latter was identified as a multiwall tube with an internal tube diameter of ∼ 12 nm and ∼ 30 walls. This maximum pressure is lowered depending on the internal tube diameter and the number of walls. We then identify a tube diameter domain in which the radial mechanical stability can be treated as equivalent to macroscopic tubes, known to be described by the canonical Lévy-Carrier law. This multiscale behavior is shown to be in good agreement with experiments on the collapse of O-rings, proposed as a simple macroscopic parallel to nanotubes in this domain. Graphical abstract: Image 1